Neurological Manifestations of hospitalized patients with mild to moderate infection with SARS-CoV-2 Omicron variant in Shanghai, China. Issue 2 (February 2023) - Shen, Xiaolei; Wang, Ping; Shen, Jun; Jiang, Yuhan; Wu, Li; Nie, Xin; Liu, Jianren; Chen, Wei
Abstract: Background: Accumulating studies demonstrated that patients with coronavirus disease 2019(COVID-19) could develop a variety of neurological manifestations and long-term neurological sequelae, which may be different from the strains. At the peak of the Omicron variant outbreak in Shanghai, China, no relevant epidemiological data about neurological manifestations associated with this strain was reported. Objective: To investigate neurological manifestations and related clinical features in patients with mild to moderate COVID-19 patients with Omicron variant. Methods: A self-designed clinical information registration form was used to gather the neurological manifestations of mild to moderate COVID-19 patients admitted to a designated hospital in Shanghai from April 18, 2022 to June 1, 2022. Demographics, clinical presentations, laboratory findings, treatments and clinical outcomes were compared between patients with and without neurological manifestations. Results: One hundred sixty-nine(48.1 %) of 351 patients diagnosed with mild to moderate COVID-19 exhibited neurological manifestations, the most common of which were fatigue/weakness(25.1 %) and myalgia(20.7 %), whereas acute cerebrovascular disease(0.9 %), impaired consciousness(0.6 %) and seizure(0.6 %) were rare. Younger age( p  = 0.001), female gender( p  = 0.026) and without anticoagulant medication( p  = 0.042) were associated with increasing proportions of neurological manifestations as revealed by multivariate logistic regressions. Patients with neurological manifestations had lower creatine kinase and myoglobin levels, as well as higher proportion of patchy shadowing on chest scan. Vaccination status, clinical classification of COVID-19 and clinical outcomes were similar between the two groups. Conclusions: Nearly half of the involved patients have neurological manifestations which were relatively subjective and closely associated with younger age, female gender and without anticoagulation. Patients with neurologic manifestations may be accompanied by increased lung patchy shadowing.